2021
DOI: 10.3390/ani11082255
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Etiology, and Risk Factors of Clinical Mastitis in Dairy Cows under Semi-Tropical Circumstances in Chattogram, Bangladesh

Abstract: Clinical mastitis (CM) is an important production disease in dairy cows, but much of the knowledge required to effectively control CM is lacking, specifically in low-income countries where most farms are small and have specific dairy management, such as regular udder cleaning and practicing hand milking. Therefore, we conducted a 6-month-long cohort study to (a) estimate the incidence rate of clinical mastitis (IRCM) at the cow and quarter level, (b) identify risk factors for the occurrence of CM, (c) describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Studies of milk from sick cows for the clinical form of mastitis on farms in Bangladesh have shown high resistance of Escherichia coli to Amoxicillin, Ampicillin, and Tetracycline [31], [42]. Studies conducted in Canada indicate that this isolate was insensitive to Streptomycin, Tetracycline, Ampicillin, and Colistin, but showed sensitivity to Ciprofloxacin and Gentamicin [33] According to the authors [32], more than 60% of isolates of E. coli showed resistance to Oxacillin and Sulfamethoxazole-trimethoprim.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of milk from sick cows for the clinical form of mastitis on farms in Bangladesh have shown high resistance of Escherichia coli to Amoxicillin, Ampicillin, and Tetracycline [31], [42]. Studies conducted in Canada indicate that this isolate was insensitive to Streptomycin, Tetracycline, Ampicillin, and Colistin, but showed sensitivity to Ciprofloxacin and Gentamicin [33] According to the authors [32], more than 60% of isolates of E. coli showed resistance to Oxacillin and Sulfamethoxazole-trimethoprim.…”
Section: Resultsmentioning
confidence: 99%
“…Mastitis is currently one of the main health problems of dairy cows, despite the increasing advances in technology and veterinary measures. The incidence of mastitis is, of course, highly dependent on the lactation stage [ 7 , 33 ]. In our study, we monitored the prevalence and etiology of mastitis in four dairy farms during the early lactation phase.…”
Section: Discussionmentioning
confidence: 99%
“…According to Singha et al [ 7 ], CM represents a serious health problem that can result in the reduction of milk yield, milk quality deterioration, treatment costs, involuntary culling, death, increased risk of antimicrobial resistance, and reduced animal welfare. Therefore, the prevalence of CM should be at the lowest level in lactating cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, mastitis is one of the major limitations in successful dairy farming, with an overall prevalence of 19.9% and 44.8% of mastitis cases in dry and wet seasons, respectively [ 9 ]. A recent study using a larger cohort of dairy cows from the Chottogram district of Bangladesh showed a 43.9% incidence rate of clinical mastitis [ 10 ]. Metabolic diseases can produce acute, temporary, but potentially fatal conditions in animals.…”
Section: Introductionmentioning
confidence: 99%